If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -7 + 44y Solving 15 = -7 + 44y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-44y' to each side of the equation. 15 + -44y = -7 + 44y + -44y Combine like terms: 44y + -44y = 0 15 + -44y = -7 + 0 15 + -44y = -7 Add '-15' to each side of the equation. 15 + -15 + -44y = -7 + -15 Combine like terms: 15 + -15 = 0 0 + -44y = -7 + -15 -44y = -7 + -15 Combine like terms: -7 + -15 = -22 -44y = -22 Divide each side by '-44'. y = 0.5 Simplifying y = 0.5
| -100=x^2-29x | | 10x=1+5x | | 14+12y=16+9y | | .25x+9=1 | | 28-7x=-28x-28 | | X-13.6=-16 | | 12x-42+3x=6(3x-9) | | -23+13n+47-5n=-28 | | 5.3+(w+1.2)= | | -2u+1.4=-0.6 | | 10x=5+1x | | -2(b+7)=3b+7-5b | | H=-16t^2+7t+28 | | 8x+5x+8+6= | | 8-1-(18-2)/8= | | X-2y=3z | | 31-(2x+3)=2(x+4)+x | | 90+x*86=45x+8 | | -5(w+3)=-7w-35 | | -20-f=20-6f+20 | | 7(2x-1)=-3(5x-3) | | 3x+2(-6+2)=-86 | | 12x+y=60 | | m^2+11m+28=0 | | 61=10t-4.9t^2 | | 90+x*291=91 | | 3x-9-12=3 | | v-9=-7v+7 | | 1-1/5= | | 4x^2+48x+108=0 | | 3(8x-4)=6(4x-2) | | [x]-14=21 |